Penguatan Pendidikan Karakter Peserta Didik Melalui Bimbingan dan Konseling Islam - Muhammad Zidan Nur Ihsan; Zulfa Iftinani Muchtar; Abid Daffa Khairullah; Hanifah Miftahul Janah; Novi Novita Ramandani (Pendagogia: Jurnal Pendidikan Dasar, 2024)
The urgency of character education has become a very popular issue in educational settings. The importance of character education is because character is a foundation that shapes the culture of social life and builds a civilization. Therefore, education as the main actor develops 3 (three) sub-systems which include: First, Administration. Second, teaching. Third, providing and developing student character. So, to realize the third sub-section regarding the provision and development of student character, the school created Islamic guidance and counseling management. However, in order to achieve perfect strengthening of student character, it must be accompanied by a good, systematic process. Starting from planning, the process of mobilizing human resources, monitoring, and assessing guidance and counseling activities. This research aims to find out how character is strengthened through Islamic counseling, and the role of counseling in character education. The results of this research show that the role of counseling in strengthening students' character is very influential. This is supported by the correct methods and approaches, so that the message or thing that is wanted to be built in character education can be conveyed effectively and efficiently